Fertility preservation by conservative approach in a primiparous woman with placental adherence - Dsouza, Lovline M.; Murali, Akshaya; Thomas, Annamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Placenta accreta spectrum (PAS) describes a group of disorders in which all, or part of the placenta remains adherent to the uterine wall. Early identification of risk factors, accurate diagnosis and treatment in accordance with the resources available are essential and can help in reducing maternal morbidity and mortality. In the absence of risk factors, placental adherence is a rare entity, and conservative management becomes essential, especially in primiparous women to preserve future fertility. A primigravida in her late twenties presented in labour at 35 weeks of pregnancy to deliver a live baby of 2200 gm. The placenta did not separate with uterotonics and multiple attempts at manual removal of placenta under general anaesthesia. Medical management to conserve the uterus was decided, and two doses of methotrexate (50 mg) were given intramuscularly a week apart. Placental products were expelled after 2 months and the patient resumed her normal menses. She conceived spontaneously 8 months later. PAS is a possibility, though rare, in low-risk primigravidae and preparedness to confront such situations is of utmost importance. Intramuscular single dose or multiple dose methotrexate can be considered as a viable option in stable patients who wish to retain their fertility.